System of stunting information centre development using waterfall method - Paradise, Paradise; Amrustian, Muhammad Afrizal (Jurnal Mandiri IT, 2024)
Stunting is a condition in which the development and growth of children are stunted due to malnutrition. In Indonesia, 21.6% of the approximately 300 million stunting cases still exist. In an endeavour to combat stunting, the Indonesian government is holding posyandu at the lowest levels of government. Despite these efforts, a significant number of parents do not receive information about stunting. Therefore, this study will develop a web-based information application about stunting. The application is developed using the cascade methodology. The conclusion of this analysis was that the waterfall methodology is still applicable for small development teams. The application can then provide information on child development and malnutrition at any time.